Communication Challenges and Needs in the Multilingual Workplace: The Case of Security Officers in Jababeka Area Indonesia - Pujiastuti, Ani; Mahmud, Yogi Saputra; Herdiansyah, Haris (Komunitas, 2022)
Modern-time workplaces have become increasingly international and multilingual due to the presence of workers from different ethnicities, languages, and cultural backgrounds.  Due to the lack of training programs that are mainly focused on developing communication skills, security officers have faced challenges in communicating with clients, especially those who work in multilingual workplaces. This research aims to investigate the challenges of the workers in communicating in a multilingual workplace and exploring the perceived needs of the workers. This research was conducted in Jababeka Area Industries Jakarta. The research found various challenges and needs faced by the security officers including challenges with their occupational standing, limited training, inadequate workplace support system, and limited access and resources for learning. The security officers realize that the ultimate goal of communication in foreign language in the workplace is not merely shown by correctness and perfection, but how messages are transferred and how instructions are understood.